2008
DOI: 10.2340/16501977-0245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance training in combination with coenzyme Q10 supplementation in patients with post-polio: a pilot study

Abstract: There was no effect of coenzyme Q10 supplementation during resistance training on post-polio syndrome symptoms. Thus, supplementation with coenzyme Q10 has no beneficial effect on muscle function in patients with post-polio syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 6 publications
0
15
0
1
Order By: Relevance
“…However, in a randomized trial of post‐polio patients, the combination of resistance training and coenzyme Q10 did not result in improvements in muscle strength, endurance, or quality of life in the coenzyme Q10 group . Creatine has been studied in NMD because it increases skeletal muscle mass in healthy exercising individuals and also reduces ATP loss during heavy anaerobic exercise by supplying more phosphocreatine to the muscle . However, there have been mixed results in NMD, as it seems cause a significant increase in strength in muscular dystrophy patients compared with placebo, but not in metabolic myopathies …”
Section: New Approaches To Exercise Training In Nmdmentioning
confidence: 99%
“…However, in a randomized trial of post‐polio patients, the combination of resistance training and coenzyme Q10 did not result in improvements in muscle strength, endurance, or quality of life in the coenzyme Q10 group . Creatine has been studied in NMD because it increases skeletal muscle mass in healthy exercising individuals and also reduces ATP loss during heavy anaerobic exercise by supplying more phosphocreatine to the muscle . However, there have been mixed results in NMD, as it seems cause a significant increase in strength in muscular dystrophy patients compared with placebo, but not in metabolic myopathies …”
Section: New Approaches To Exercise Training In Nmdmentioning
confidence: 99%
“…Furthermore, one may expect more extensive research with follow-up in a non-life-limiting condition. With regard to postpolio syndrome, despite a number of intervention trials [28][29][30][31][32][33] , the lack of reported incidence/prevalence may reflect difficulties in confirming diagnoses due to the symptoms being similar to those associated with natural ageing. Accurate case ascertainment would be difficult and expose statistics to bias.…”
Section: Non-reported Conditionsmentioning
confidence: 99%
“…Muscle strength, muscle endurance and quality of life increased statistically significantly in all 14 patients but there was no significant difference between the CoQ 10 and placebo groups (Kough et al, 2008).…”
Section: Average Daily Intake Through Diet = 3 To 5 Mg (Webermentioning
confidence: 81%